The importance of career in human resource development - Chagelishvili, Ana; Surmanidze, Natia; Patsatsia, Konstantine (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Human resource development and career development are essential issues for a person's self-realization and effective functioning of the organization. Human resource development is often perceived as a necessary condition for career success; however, less attention is paid to the importance and the role of a career in human resource development. The study aims to highlight the importance of career in human resource development. To achieve this goal, the documentary analysis method was used, during which the above hypothesis was tested on the basis of analysis and synthesis techniques. The study revealed the key role of career development in human resource development and identified their interrelated issues. This paper, which forms the theoretical basis for future research, will be useful to all interested parties in the given issues.